1994
DOI: 10.1111/j.1365-2141.1994.tb05022.x
|View full text |Cite
|
Sign up to set email alerts
|

The differences in quantities of α2‐and α1‐globin gene variants in heterozygotes

Abstract: We have identified through sequencing of amplified DNA the mutations in the alpha 2- and alpha 1-globin genes in 63 individuals with a heterozygosity for an alpha chain abnormal haemoglobin (Hb). Moreover, we developed a reverse transcription/polymerase chain reaction (RT/PCR) based procedure for the determination of the alpha 2- and alpha 1-mRNA ratio in normal individuals. The numbers of alpha 2 and alpha 1 variants were nearly the same. The average percentage of the abnormal Hb in heterozygotes with alpha 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 54 publications
5
38
1
Order By: Relevance
“…In the present study, we showed that HbO is stable in vitro, consistent with the previous study of Molchanova et al (1994). An α1-globin gene carrying a HbO mutation is transcribed normally, and its mRNA represents around 21% of the total Hb mRNA (Molchanova et al 1994).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the present study, we showed that HbO is stable in vitro, consistent with the previous study of Molchanova et al (1994). An α1-globin gene carrying a HbO mutation is transcribed normally, and its mRNA represents around 21% of the total Hb mRNA (Molchanova et al 1994).…”
Section: Discussionsupporting
confidence: 78%
“…The replacement of negatively charged glutamic acid by positively charged lysine at residue 116 is structurally significant and thus could potentially lead to a functional or assembly defect. The HbO level in all but two of our cases was in fact found to be significantly lower (10.1% to 13.8%) than that expected from a stable α 1 -globin variant; stable α 1 -variants have been reported to be present in the range of 16.9% to 22.5% (Molchanova et al 1994). The level of HbO has been determined previously in two studies only.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Total globin chain content and the rate of protein synthesis was determined by labeling immature red cells with 3 H-leucine and separation of the globins by HPLC (6); as plasma erythropoietin and red cell DPG concentrations were determined by RIA (7) and an enzymatic method, respectively (8). Finally, DNA and mRNA analysis was carried out on the samples as described below.…”
Section: Methodsmentioning
confidence: 99%